PROSES PEMEROLEHAN BAHASA DARI ANAK-ANAK SAMPAI SEKOLAH DASAR: KAJIAN PSIKOLINGUISTIK - Jamilah; Beru Ginting, Sri Dinanta; Br Surbakti, Ernawati; Wahdaniah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study of the process of language acquisition is part of Psycholinguistics as a field of study that connects psychology with linguistics, with a focus on the mental processes involved in the acquisition, use and understanding of language. Psycholinguistics is very important because it discusses the problems of language acquisition, the relationship between language knowledge and language use, and the process of producing and understanding speech. Through psycholinguistics, the language used needs to be structured and have elements of good grammar.